The Armenian Community of Uruguay - Minasyan, Arevshat (History and Culture, 2021)
The following paper represents the story of Uruguay’s Armenian community formation from the very first establishment of Armenian community to present days. This article discusses handful of significant patriotic manuals, which were carried out by Armenian community of Uruguay. The article consists of five parts; the first part represents the initial establishment of Armenian community, some chronological calculations, the main reasons and prerequisites for the establishment of Armenian community. The second part represents the formation of Armenian community. Then it speaks about the educational, socio-political structures that function within the community and about manuals carried out by cultural centers, which have a huge impact on the preservation of Armenian Identity. The goal of this paper is to raise the awareness of the importance of Armenian community in the context of Homeland – Diaspora relationship.